PENGINTEGRASIAN PENDIDIKAN KARAKTER BERBASIS ALQUR’AN DALAM PEMBELAJARAN IPA BAGI MAHASISWA PGSD STKIP MUHAMMADIYAH MUARA BUNGO - megawati megawati; Randi Eka Putra (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
This research was motivated by the problem of the low character values shown by students during science learning. So far, science learning has emphasized the aspects of cognition and has not promoted the importance of planting character values ​​in learning. A change in the teaching paradigm is deemed necessary where it is necessary to align the conceptual mastery and character improvement. The character values developed in science learning can be based on the Al-Qur'an. Because basically character values ​​come from religious values. The purpose of this study was to describe the learning tools, the implementation of learning, the advantages and disadvantages of the integrated learning system of character education based on the Qur'an in science learning for students of PGSD STKIP-MB. This research was conducted at STKIP-MB, with the research subjects being students of the PGSD Study Program semester II of the 2019/2020 Academic Year. This type of research is a descriptive study using a quantitative approach. The results of the research obtained the suitability of the RPS reached 91.07%. This means that it has shown an integration of planting character values ​​based on the Qur'an in the components of the RPS. Apart from that, from the results of the questionnaire analysis, the percentage of success in cultivating character education based on the Qur'an in students reached 82.35%. This means that after learning science through the integration of character education based on the Qur'an, it has a positive effect on the personal development of students, where the character values ​​in students can be built very well.